IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA (K3): PENGABDIAN MASYARAKAT KEPADA UNIT KEGIATAN MAHASISWA PENCAK SILAT - Mirza, Muhammad Navis (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2023)
Occupational Health and Safety (OHS) in Pencak Silat, a traditional martial art, is essential to ensure safety and well-being of practitioners during training and competitions. OHS in sports refers to a set of measures and practices designed to identify, prevent, and reduce risks of injury or health damage that may arise during activities. Pencak Silat is a martial art with deep roots in the cultural heritage of Southeast Asian countries, particularly Indonesia. It involves combat movements such as strikes, kicks, throws, and grappling, which can lead to injuries if not performed correctly or without appropriate protective gear. Community Service to participants in pencak silat student activity unit is carried out at 10 June & 17 June 2023 using training method that highlighting key points regarding OHS in Pencak Silat such as, risk assesment, protective equipment, provision of safe facilities, adequate supervision, emergency preparedness, and continuous improvement. The output of this community service is publication in scientific journals & Poltekun pencak silat participants can gain knowledge of OHS to be applied when practicing or competing. By emphasizing OHS in Pencak Silat, a safe and healthy environment can be created, allowing practitioners to train and compete with confidence, enhance their skills, and promote Pencak Silat as a whole.